2019
DOI: 10.1098/rsob.190043
|View full text |Cite
|
Sign up to set email alerts
|

Models and mechanisms of the rapidly reversible regulation of photosynthetic light harvesting

Abstract: The rapid response of photosynthetic organisms to fluctuations in ambient light intensity is incompletely understood at both the molecular and membrane levels. In this review, we describe research from our group over a 10-year period aimed at identifying the photophysical mechanisms used by plants, algae and mosses to control the efficiency of light harvesting by photosystem II on the seconds-to-minutes time scale. To complement the spectroscopic data, we describe three models capable of describing the measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 83 publications
1
36
0
Order By: Relevance
“…Research on simulation of the energy dissipation are based on two principle theories defined by Demmig-Adams et al [20] that were drawn up on the basis of puddle model of energy transfer, in which the light energy absorbed in antennae chlorophyll is always transferred to the same reaction centers, and by Kramer et al [25] and Hendrickson et al [26] that made on the basis of the lake model of energy transfer, in which the excitation energy of chlorophylls can be exchanged among reaction centers. In fact, what distinguishes these two models is how far excitation energy can travel before it is captured at a reaction center or is dissipated by other means [27]. From this perspective, in this study, we worked on some of the most important photo-protective energy dissipation parameters that have been introduced so far.…”
Section: Discussionmentioning
confidence: 99%
“…Research on simulation of the energy dissipation are based on two principle theories defined by Demmig-Adams et al [20] that were drawn up on the basis of puddle model of energy transfer, in which the light energy absorbed in antennae chlorophyll is always transferred to the same reaction centers, and by Kramer et al [25] and Hendrickson et al [26] that made on the basis of the lake model of energy transfer, in which the excitation energy of chlorophylls can be exchanged among reaction centers. In fact, what distinguishes these two models is how far excitation energy can travel before it is captured at a reaction center or is dissipated by other means [27]. From this perspective, in this study, we worked on some of the most important photo-protective energy dissipation parameters that have been introduced so far.…”
Section: Discussionmentioning
confidence: 99%
“…Polivka and Frank [ 60 ] elaborated on the difficulties of studying these mechanisms due to the impact of the microenvironment on the photophysical properties of photosynthetic pigments. Since then, Graham Fleming’s group conducted fluorescence lifetime studies in vivo in an intact photosynthetic organism and concluded that zeaxanthin was involved in both of the two different photophysical mechanisms (energy transfer and charge transfer) capable of de-exciting chlorophyll thermally [ 61 , 62 ]. The last portion of the foreword from Krinsky (in [ 24 ]) addresses parallels between a leaf and a human eye that accumulates dietary zeaxanthin: “whether a similar process occurs in the macula area of the primate retina, where zeaxanthin is concentrated, is not known.”…”
Section: Xanthophyll Cycle Conversion State and Dissipation Of Unumentioning
confidence: 99%
“…Although NPQ is nowadays a well-established concept in photoregulation of many photosynthetic organisms, a complete identification of the exact molecular mechanisms is still missing. What seems more realistic is that there is not a unique mechanism but different strategies that the various types of antenna complexes have optimized [5][6][7][8]. Both the major LHCII antenna of PSII and the minor antennas, in particular CP29, have been shown to participate in NPQ [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%